Investigation of self-regulated learning (SRL) strategies used by gifted students while learning science - Koçoğlu, Merve. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
In this study, a group of students who were identified as gifted were investigated to have a deeper understanding of their self-regulated learning skills. 32 gifted students were investigated while they were trying to learn two scientifıc concepts by watching two video elips. Qualitative data were obtained by interviews and open-ended questions which requires written responses and drawings. Also, students' notes and drawings that they have taken while watching videos were analyzed. Qualitative data showed that mostly stated cognitive strategies were low level strategies such as rehearsal and content reproduction strategies and mostly stated metacognitjve strategies were monitoring and self-evaluation. Quantitative data was obtained from Metacognitive Awareness lnventory (Karakelle and Saraç, 2007) and by scoring students' responses to interviews and open-ended questions. Quantitative analysis results showed that no correlations were found between students' MAI scores and post-test content knowledge for both of the science videos. Also, none of the self-regulated groups differed in terms of increase in the content knowledge scores. Correlations were obtained between metacognitive skills and students' science goals, searching for new informational resources, having a systematic studying habits and regular scheduled studying habits.
Keywords: Learning strategies.; Learning -- self-regulation.